Avaliação fisico-química de queijo de coalho misto de leite de cabra e vaca em diferentes proporções - Costa, Andrezza Maria Freire da (Universidade Federal Rural do Semi-Árido, 2021)
The objective of this research was to evaluate the physical-chemical characteristics of mixed rennet cheese produced with goat and cow's milk in different proportions. An average of 800 grams of cheese were produced for each treatment. The treatments analyzed were T1(25% cow's milk and 75% goat's milk), T2(50% goat's milk and 50% cow's milk) and T3(25% goat's milk and 75% cow's milk). cheeses were elaborated following the pattern of making rennet cheese. The physicochemical characteristics of rennet cheeses, pH, acidity, moisture, fat, ash and instrumental, hardness and color were analyzed. The design used was completely randomized, in which the results were submitted to analysis of variance (ANOVA) and, in case of significant differences, the Tukey test at 5% significance. Fat varied, with lower content in T1. The pH varied between treatments, being more acidic in T3. The moisture content increased according to the inclusion of cow's milk. In the color analysis, for parameters L* and a* there were significant differences between treatments. The production of mixed rennet cheese from goat and cow's milk in different proportions, promotes variations in the physical- chemical and instrumental characteristics of the product. These characteristics are attractive to the consumer market, which can strengthen the regional goat farming chain.
Keywords: Queijo de coalho misto; Caprino; Bovino; Características físico-químicas; Mixed rennet cheese; Goat; Bovine; Physical-chemical characteristics; CIENCIAS AGRARIAS::ZOOTECNIA